2010
DOI: 10.1007/s00068-010-0043-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between depressive mood and pain amongst individuals with limb amputations

Abstract: The results of this study revealed the validity of optional approaches such as prescription of antidepressants or psychological counseling to improve mental health of individuals with limb amputations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
7
1
1
Order By: Relevance
“…Trauma and changes in physical body characteristics are risk factors for depression [12], and TLA leads to permanent changes in physical appearance or function. Young traumatic amputees tend to get worse psychologically with increasing time since amputation as compared with older amputees [1,2,13]. Our findings therefore agree that the risk of psychological consequences of TLA is substantial.…”
Section: Discussionsupporting
confidence: 80%
“…Trauma and changes in physical body characteristics are risk factors for depression [12], and TLA leads to permanent changes in physical appearance or function. Young traumatic amputees tend to get worse psychologically with increasing time since amputation as compared with older amputees [1,2,13]. Our findings therefore agree that the risk of psychological consequences of TLA is substantial.…”
Section: Discussionsupporting
confidence: 80%
“…A large majority of the patients with complaints of depression reported that they had to undergo amputation owing to work-related trauma, and patients in this group also stated that their most significant complaint was pain in the amputated extremity. 26 In our study group, the rate of patients with depressive symptoms was 37.1%. The lack of difference in the depression scores between patients who have undergone amputations at different levels may be related with the using prostheses for walking.…”
Section: Discussionmentioning
confidence: 54%
“…The severity of depression in previous studies in which amputees were evaluated with BDI-II has been observed as 12.7-23.2% moderate and 7.3-10.1% severe. [20][21][22] The rate of extremely severe depression was reported as 8.2%. 20 In this study, only 6.5% of the patients had severe depression and 8% had moderate depression, indicating that the Syrian refugee amputees were partially in a good condition based on BDIS.…”
Section: Discussionmentioning
confidence: 99%
“…The patient is asked to choose the statement that best describes how he/she felt during the last week, including the day of the survey. 17 Depression levels according to the total score obtained from the answers of all questions are defined as minimal (0-13), mild (14)(15)(16)(17)(18)(19), moderate (20)(21)(22)(23)(24)(25)(26)(27)(28) and severe (29-63). 18 The validity study of the Arabic version of the inventory was conducted by Ghareeb.…”
Section: Methodsmentioning
confidence: 99%